The Street as Pre-requisite Open Space: Current South African Settlement Practice and the Need for a Paradigm Shift - Fabio Todeschini; David Dewar (Proekt Bajkal, 2013)
In contexts experiencing rapid urbanization, such as South Africa, qualitatively fine open space is essential as that is where much of life is lived. However, the continued application of a modernist town-planning paradigm perversely tends to block the necessary shift in thinking. This is particularly exemplified in movement channels, which typically account for about a quarter of urban areas. The seminal distinction that has been lost is that between ‘road’ and ‘street’.